Principle component analysis for the classification of fingers movement data using dataglove "glovemap" - Nazrul H., Adnan; Wan Khairunizam, Wan Ahmad, Dr.; Shahriman, Abu Bakar, Dr.; Juliana Aida, Abu Bakar (International Association for Engineeering and Management Education, 2013)
Link to publisher's homepage at http://www.iaeme.com/